2024
DOI: 10.1029/2023gl106114
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and NAO Linkage to Strong Volcanism and Associated Post‐Volcanic High‐Latitude Winter Warming

Muhammad Mubashar Dogar,
Masatomo Fujiwara,
Ming Zhao
et al.

Abstract: High‐latitude winter warming was observed following strong tropical volcanism, which has long been believed to be due to the volcanic‐induced positive North Atlantic Oscillation (NAO) phase. However, recent works argue that this warming is caused by El Niño–Southern Oscillation (ENSO) variability instead of volcanoes. Moreover, some studies further argue that El Niño and volcanoes work together to produce this post‐volcanic NAO winter warming. To better understand these arguments on post‐volcanic high‐latitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Studies based on proxy reconstructions and climate models have shown that El Niño-like conditions are common in the equatorial Pacific 0-2 years following explosive eruptions (Adams et al, 2003;Dogar et al, 2024;Emile-Geay et al, 2008;Pausata et al, 2020;Stevenson et al, 2016;Tiger & Ummenhofer, 2023), although models may have a tendency to overestimate this effect (Dee et al, 2020). In CESM1, there is a much higher probability (up to 44%) of El Niño like SSTs in the equatorial Pacific in the second year following tropical eruptions and 1-2 years following northern eruptions (Table S1 in Supporting Information S1), relative to non-eruption years.…”
Section: Impact Of Volcanic Eruptions On Enso-hjl Relations In Cesm1mentioning
confidence: 99%
“…Studies based on proxy reconstructions and climate models have shown that El Niño-like conditions are common in the equatorial Pacific 0-2 years following explosive eruptions (Adams et al, 2003;Dogar et al, 2024;Emile-Geay et al, 2008;Pausata et al, 2020;Stevenson et al, 2016;Tiger & Ummenhofer, 2023), although models may have a tendency to overestimate this effect (Dee et al, 2020). In CESM1, there is a much higher probability (up to 44%) of El Niño like SSTs in the equatorial Pacific in the second year following tropical eruptions and 1-2 years following northern eruptions (Table S1 in Supporting Information S1), relative to non-eruption years.…”
Section: Impact Of Volcanic Eruptions On Enso-hjl Relations In Cesm1mentioning
confidence: 99%